Penentu Fee Audit Pada Perusahaan Manufaktur - Maylia Pramono Sari; Novi Wijayaningsih; Surya Raharja (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to analyze the effect of Chief Executive Officer (CEO) gender and ownership structure on audit fees and the moderating effect of firm size. Methodology/approach: The population used are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019, with a total of 192 companies. This study uses descriptive analysis and inferential analysis through regression analysis with moderating variables using the absolute difference value test. Findings: The results show that CEO gender has a significant negative effect on audit fees, foreign ownership has a significant positive impact on audit fees. In contrast, managerial ownership and government ownership have no significant impact on audit fees. Firm size can moderate in weakening the effect of CEO gender on audit fees but cannot moderate the effect of managerial ownership, foreign ownership, and government ownership on audit fees. Originality/value: This study adds an independent CEO gender variable and a moderating variable in company size.